Biological risk posed by internal tooth whitening - Alain Manuel Chaple Gil; Eduardo Maximiliano Fernandez Godoy; Lisandra Quintana-Muñoz; Cristian Bersezio (Editorial Ciencias Médicas, 2021)
Introduction: Internal tooth whitening has been a component of dental practice for several decades, but biological risks have been described about which not much evidence is available. Objective: Describe the biological risks posed by internal tooth whitening in nonvital teeth. Methods: An exploratory systematic review was conducted in the bibliographic database PubMed using Boolean operators and key words obtained from Health Sciences Descriptors. The variables analyzed were main author, title, year of publication, article type, journal where the articles were published and biological risk of the internal tooth whitening procedure described. Results were filtered and processed in a database and full texts were analyzed for quality and compliance with the inclusion and exclusion criteria. Results: A total 14 articles were included in the study, all of which were either original studies or systematic reviews. In 64.3% of the articles, findings had to do with the presence of external cervical resorption after internal tooth whitening. The remaining articles did not contribute any evidence of biological risks after the treatment described. Conclusions: More than half of the articles included in the study concluded that external cervical resorption is the main biological risk posed by internal whitening of nonvital teeth, supported by the triggering factor of a history of dental trauma leading to the occurrence of these disorders.